Technical Change, Job Tasks, and Rising Educational Demands: Looking outside the Wage Structure - Spitz‐Oener, Alexandra (Journal of Labor Economics, 2006)
Empirical work has been limited in its ability to directly study whether skill requirements in the workplace have been rising and whether these changes have been related to technological change. This article answers these questions using a unique data set from West Germany that enabled me to look at how skill requirements have changed within occupations. I show that occupations require more complex skills today than in 1979 and that the changes in skill requirements have been most pronounced in rapidly computerizing occupations. Changes in occupational content account for about 36% of the recent educational upgrading in employment.